2020
DOI: 10.14744/scie.2020.37929
|View full text |Cite
|
Sign up to set email alerts
|

Dose Dependent Effects Of Lithium Carbonate On Rat Thyroid Hormones, Parathormon and Calcium Levels With Thyroid Tissue

Abstract: The aim of this research was to investigate the effects of subacute use of lithium carbonate (Li 2 CO 3 ), on serum T3, T4, thyroid stimulating hormone (TSH), parathyroid hormone (PTH) and calcium (Ca) levels and thyroid tissue. In addition, this research is important as one of the rare studies in which thyroid tissue was subjected to histological examination.Methods: Thirty-two male Sprague Dawley rats were assigned into groups consisting of eight animals each, based on weight; Group 1: Sham control, Group 2:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…LC shows five times greater concentration in the thyroid gland than in other organs (McDermott et al, 1986). LC may reduce the uptake of iodine by the thyroid gland, prevent iodotyrosinase coupling, and antagonize hormone release from the gland (Topcu, 2020). This could be attributed to the reduction of colloidal pinocytosis from the follicular lumen, which could impair colloid droplet formation (van der Vaart et al, 2021), as observed by PAS staining.…”
Section: Discussionmentioning
confidence: 99%
“…LC shows five times greater concentration in the thyroid gland than in other organs (McDermott et al, 1986). LC may reduce the uptake of iodine by the thyroid gland, prevent iodotyrosinase coupling, and antagonize hormone release from the gland (Topcu, 2020). This could be attributed to the reduction of colloidal pinocytosis from the follicular lumen, which could impair colloid droplet formation (van der Vaart et al, 2021), as observed by PAS staining.…”
Section: Discussionmentioning
confidence: 99%